Adipose tissue arachidonic acid and the metabolic syndrome in Costa Rican adults - Williams, Erick S. (2007)
Arachidonic acid, a precursor to a series of inflammatory mediators, may contribute to the development of insulin resistance. We examined the association between adipose tissue arachidonic acid and the metabolic syndrome in Costa Rica, a country in which the metabolic syndrome is highly prevalent. Methods The 484 study participants each provided a fasting blood sample and an adipose tissue biopsy that was analyzed for fatty acid composition. Criteria for the metabolic syndrome were those established in the Third Report of the National Cholesterol Education Program Expert Panel. The data were analyzed by multivariate logistic regression. Results Subjects with greater adipose tissue arachidonic acid content had an increasing risk of the metabolic syndrome across quintiles: odds ratio (95% confidence interval), 1.00; 1.51 (0.78–2.91); 2.40 (1.26–4.55); 3.50 (1.84–6.66); and 6.01 (3.11–11.61); test for trend, P<0.0001, after adjustment for age, gender and area of residence. Further adjustment for metabolic risk factors, including adipose fatty acids and body mass index, did not significantly modify the result. Adipose tissue arachidonic acid was also independently associated with abdominal obesity, hypertriglyceridemia, elevated fasting glucose, and high blood pressure. Conclusions This study identifies arachidonic acid as an important independent marker of metabolic dysregulation. A better understanding of the role of this fatty acid in the pathogenesis of the metabolic syndrome is warranted.